Being Deceived: Information Asymmetry in Second‐Order False Belief Tasks. (10th August 2019) - Braüner, Torben; Blackburn, Patrick; Polyanskaya, Irina
Abstract : Braüner, Blackburn and Polyanskaya relate children's being deceived to their theory of mind skills. Second‐order false‐belief tasks are often used to test children's second‐order theory of mind development. The article gives a logical analysis of the reasoning needed to solve four types of second‐order false belief tasks, distinguished on whether a story character is deceived, and on whether the story hinges on facts in the world changing. The principle of inertia plays an important role. [74] Abstract: We analyze four well‐known second‐order false belief tasks. Superficially, all four tasks share a common logical structure: All are based around a principle of inertia, which says that an agent's beliefs are preserved over time, unless the agent receives information to the contrary. However, a deeper analysis reveals details that are both suggestive and puzzling. First, the four tasks exemplify all four possibilities inherent in the two dimensions of being‐deceived versus not‐being‐deceived and change‐in‐world versus change‐in‐belief‐only . Second, there is a feature common to all four tasks: All come with a "built in" first‐order false belief. We call these inner first‐order false beliefs . They introduce an informational asymmetry that has the same logical form in all four tasks, but whose role is unclear. We do two things in this paper. First, we show that inner first‐order false beliefs play an important (though seemingly unremarked) role in the experimental design of the tasks. Second, we present some empirical results (for both typically developing children and children with Autism Spectrum Disorder) on the effects of being‐deceived versus not‐being‐deceived and change‐in‐world versus change‐in‐belief‐only on second‐order reasoning ability.